The Surgical Treatment of Hallux Valgus Utilization Minimally Invasive and Percutaneous Techniques with a Shannon Burr: A Systematic Review. Issue 1 (February 2023) - Gonzalez, Tyler; Encinas, Rodrigo; Jackson, J. Benjamin
Category: Midfoot/Forefoot; Bunion Introduction/ Purpose: Recently there has been an increase in minimally invasive surgery (MIS) for the correction of hallux valgus deformity. This systematic review aims to evaluate and present the current literature on MIS hallux valgus correction in studies reporting the use of the Shannon burr with distal metatarsal osteotomies to help establish evidence-based guidelines for surgeons utilizing this technique. Methods: Two independent authors performed a systematic literature search using the following databases: PubMed, Embase, and the Cochrane library. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) protocol and the Cochrane Handbook guidelines were followed. All studies included were published from 2008 to 2022 and included the use of the Shannon burr during distal metatarsal osteotomies minimally invasive surgery for hallux valgus and at least 12-month follow-up. The MINORS score criteria was utilized to evaluate the strength and quality of 17 studies by three authors. Statistical analysis and meta-analysis were not performed due to the heterogeneity of the included studies and the data being descriptive. Results: A total of 17 studies were reviewed. A total of 911 subjects were included, and 1088 MIS procedures were performed. The average follow-up was 23.8 (12-59.1) months. AOFAS and VAS scores improved from 52.1 (41-62.5) to 90.3 (83.3-97.1) and 4.9 (3-8.2) to 0.8 (0-1.9). Satisfaction rates were very high among the studies that reported it. The HVA, IMA and DMAA angle improved from 31.4 (23.5-44.1) to 11.1 (7-17.2).), 13.4 (8.1-18.6) to 7.3 (4.2-10.3), and 12.3 (9-16.3) to 4.1 (1-6.7). Complication rate was 16.6%. Recurrence was 2.2%. Nonunion 0.4%, infections 1.1%, nerve injury 2.2%, avascular necrosis 0%, hallux varus 0.09%, transfer metatarsalgia 0.1% and hardware removal 6.2%. Conclusion: Minimally invasive surgery for the treatment of hallux valgus utilizing the Shannon burr appears to be a safe and effective therapy with appropriate correction of the hallux valgus deformity, improvement in functional outcomes, high patient satisfaction, low recurrence, and acceptable complication rates.